Aqueous Binder Enhanced High-Performance GeP5 Anode for Lithium-Ion Batteries - He, Jun; Wei, Yaqing; Hu, Lintong; Li, Huiqiao; Zhai, Tianyou (Frontiers in Chemistry, 2018)
GeP5 is a recently reported new anode material for lithium ion batteries (LIBs), it holds a large theoretical capacity about 2300 mAh g-1, and a high rate capability due to its bi-active components and superior conductivity. However, it undergoes a large volume change during its electrochemical alloying and de-alloying with Li, a suitable binder is necessary to stable the electrode integrity for improving cycle performance. In this work, we tried to apply aqueous binders LiPAA and NaCMC to GeP5 anode, and compared the difference in electrochemical performance between them and traditional binder PVDF. As can be seen from the test result, GeP5 can keep stable in both common organic solvents and proton solvents such as water and alcohol solvents, it meets the application requirements of aqueous binders. The electrochemistry results show that the use of LiPAA binder can significantly improve the initial Coulombic efficiency, reversible capacity, and cyclability of GeP5 anode as compared to the electrodes based on NaCMC and PVDF binders. The enhanced electrochemical performance of GeP5 electrode with LiPAA binder can be ascribed to the unique high strength long chain polymer structure of LiPAA, which also provide numerous uniform distributed carboxyl groups to form strong ester groups with active meterials and copper current collector. Benefit from that, the GeP5 electrode with LiPAA can also exhibit excellent rate capability, and even at low temperature, it still shows attractive electrochemical performance.